UPAYA MEMBERIKAN INFOMASI KEPADA SISWA TEHADAP BIMBINGAN DAN KONSELING MELALUI LAYANAN BIMBINGAN KLASIKAL BAGI SELURUH SISWA SMP ISLAM NURUL YAQIN - aziz, asri; supriyadi, edi (Papanda Publisher, 2022)
The purpose of this research is to provide information regarding guidance and counseling to all students of Nurul Yaqin Islamic Middle School in the even semester of the 2021/2022 academic year. This classroom action research was conducted at Nurul Yaqin Islamic Middle School, which is located on Jl. Ciakar Ds. Leuwidulang Kec. Sodonghilir Kab. Tasikmalaya. The method used in this classroom action research is to provide several actions on classical guidance services. The research subjects were all students of classes VII, VIII, and IX. Which amounted to 356. The results show that by providing this classical guidance service, students' knowledge of guidance and counseling can improve from those who do not know at all to be better and even the responses of the students themselves are very excited, so it can be concluded both theoretically and empirically through this service. can seek new knowledge for all students, especially in the Islamic Middle School Nurul Yaqin itself regarding guidance and counseling.